Boundary behavior of the Sobolev classes with critical exponent - Afanas’eva, O.S.; Ryazanov, V.I.; Salimov, R.R. (Reports of the National Academy of Sciences of Ukraine, 2019)
The conditions for outer dilation KO(x, f ) and the boundaries of domains under which the homeomorphisms of the Sobolev classes W 1,1 loc admit a continuous or homeomorphic extension to the boundary are founded.